Build a Career in Data Science video edition - Robinson, Emily; Robinson, Emily; Nolis, Jacqueline (Manning Publications, 2020)
Full of useful advice, real-case scenarios, and contributions from professionals in the industry. Sebastián Palma Mardones, ArchDaily You are going to need more than technical knowledge to succeed as a data scientist. Build a Career in Data Science teaches you what school leaves out, from how to land your first job to the lifecycle of a data science project, and even how to become a manager. about the technology What are the keys to a data scientist's long-term success? Blending your technical know-how with the right "soft skills" turns out to be a central ingredient of a rewarding career. about the book Build a Career in Data Science is your guide to landing your first data science job and developing into a valued senior employee. By following clear and simple instructions, you'll learn to craft an amazing resume and ace your interviews. In this demanding, rapidly changing field, it can be challenging to keep projects on track, adapt to company needs, and manage tricky stakeholders. You'll love the insights on how to handle expectations, deal with failures, and plan your career path in the stories from seasoned data scientists included in the book. what's inside Creating a portfolio of data science projects Assessing and negotiating an offer Leaving gracefully and moving up the ladder Interviews with professional data scientists about the audience For learners who want to begin or advance a data science career. about the authors Emily Robinson is a data scientist at Warby Parker. Jacqueline Nolis is a data science consultant and mentor. The perfect companion for someone who wants to be a successful data scientist! Gustavo Gomes, Brightcove Insightful overview of all aspects of a data science career. Krzysztof Jędrzejewski, Pearson Highly recommended. Hagai Luger, Clarizen NARRATED BY JEROMY LLOYD.